(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: The unprecedented global pandemic that sweeps the planet is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections. To combat this pandemic, the clinical presentation as well as other epidemiological characters need to be understood clearly. Objective: To describe epidemiological and clinical characteristics, management, and outcomes of Covid-19 patients attended at the Combined Military Hospital (CMH), Dhaka. Materials and Methods: This cross sectional study was conducted at CMH Dhaka from 15 April 2020 to 31 May 2020 among purposively selected 237 COVID-19 positive patients. Data collection was done by face-to-face interview using semistructured questionnaire and medical record review. Results: Highest numbers of the respondents were in the age group of 31-40 years (37.1%) with male predominance (83.1%). About 95.6% were Muslim and 58.6% were educated up to secondary level. About 87.8% had contact with a confirmed case and having 47.7%, 37.2% and 15.1% cardiovascular, endocrine and respiratory co-morbidities respectively. Fever (34.6%) was the common presenting symptoms followed by cough (22.9%), sore throat (10.6%). Radiologically about 7.2% developed bilateral pneumonia and 5.5% having lung involvement in HRCT. Almost half of the patients (48.9%) received Ivermectine and Doxicycline as treatment. Average duration of hospital stay was 14.61 (±4.29) days. About 17.7% showed neutrophilia, 30.0% positive D-dimer test, 22.4% either sepsis or systemic infection in procalcitonin estimation, 28.3% with increased ferritin, 28.7% positive C reactive protein, 21.1% with increased LDH. Conclusion: The study findings will help the clinicians and medical administrators to understand the magnitude of the disease and take appropriate measures for its prevention. JAFMC Bangladesh. Vol 17, No 2 (December) 2021: 22-28